Prevention and Management of Spinal Cord Ischemia After Aortic Surgery: An Umbrella Review - Alexandros G. Brotis; Adamantios Kalogeras; Metaxia Bareka; Eleni Arnaoutoglou; Kostas Spanos; Miltiadis Matsagkas; Kostas N. Fountas (Brain Sciences)
Background/Objectives: Spinal cord injury is a devastating complication of aortic surgery, with significant morbidity and mortality. This review aimed to summarize the current literature on preventing and managing spinal cord ischemia after open and endovascular aortic repair. Methods: We conducted a comprehensive review of PubMed, Scopus, and the Web of Science, focusing on systematic reviews and meta-analyses of the pathophysiology, risk factors, and strategies for mitigating the risk of spinal cord injury after aortic repair. We assessed the quality of the reporting for the eligible studies using the AMSTAR-2 tool and evaluated the strength of the evidence using the GRADE approach. Due to the absence of homogeneous clinical data, the evidence was synthesized in a narrative form. Results: Spinal cord ischemia can occur after both open and endovascular aortic repair, with a higher incidence reported in more extensive thoraco-abdominal aortic aneurysm repairs. The underlying pathogenesis is largely understudied. Several preventive strategies have been partially investigated, including cerebrospinal fluid drainage, hypothermia, and distal aortic perfusion. While the employment of neuromonitoring has been established in spine surgery, its efficacy in aortic repair remains uncertain due to confounding factors like hypothermia, anesthesia medications, and cardiopulmonary bypass. The prompt management of spinal cord complications is crucial to optimizing outcomes. No clear treatment algorithm has been universally adopted. Conclusions: Spinal cord ischemia remains a major challenge in aortic surgery, with a significant impact on patient outcomes. Further research is needed to elucidate the relevant pathophysiology and develop more effective intraoperative monitoring and management strategies.